A comparison of the abrasiveness of homemade dentifrice versus the commercially available dentifrice most commonly used by UPCD students (Colgate Total) an in vitro study - Abayon, Maricelle U.; Angeles, Rosa Patricia Jay C.; Murjani, Bhabita (Adviser).
Dentifrices serve a variety of purposes. It has abrasive, detergent and polishing actions and can also be a medium for therapeutic agents to reach the teeth. This study aims to compare the abrasive properties of the homemade dentifrice formulation prepared by the researchers versus that of Colgate? Total, the commercially available dentifrice most commonly used by UPCD students, in an in vitro setting. Specifically, this study aims to determine the changes in thickness and weight of the acrylic plates after being brushed with the test solutions and to observe under a zoom microscope the surface appearance of the plates treated with the solutions, and to relate these observations with the abrasive property of the test solutions. This comparative study utilized an experimental method and a random allocation trial was employed. Ten acrylic plates were randomly assigned to each of the four test solutions: homemade dentifrice, Colgate? Total, calcium carbonate USP, and distilled water. Each plate was viewed and photomicrographed under the zoom microscope and the surface appearance was described. The thickness of each plate was measured from the center by a calibrated vernier caliper and was weighed using a calibrated digital weighing scale. The plates were mounted one at a time on the mounting stage and brushed for two minutes with the assigned test solution. The plates were rinsed, dried, and again viewed under the zoom microscope, measured and weighed. The t-test, with an a-value of 0.05, showed that the mean difference between the thickness and weight of the homemade dentifrice and Colgate? Total were not significant. This is in support of the findings of similar studies, like that of Epstein et al. The abrasion properties of homemade dentifrice is comparable to that of Colgate? Total. With further testing, the homemade dentifrice may be considered an alternative to Colgate? Total.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentifrices